Early atypical MRI findings in a pediatric patient with Neuro-Behçet’s disease - Sihan Wang; Qi Shan; Jiawen Tang; Fan Xia; Jinyang Zhao; Xiaohong Lyu (BMC Neurology)
Abstract Behçet’s disease (BD) is a multi-system recurrent inflammatory disease. Neuro-Behçet’s disease (NBD), as a severe and rare manifestation of BD, is frequently misdiagnosed in its early stages. Pediatric NBD poses diagnostic challenges due to its insidious onset, highlighting the critical role of neuroimaging. This report describes a pediatric patient with atypical early clinical manifestations and magnetic resonance imaging (MRI) findings. The patient initially presented without mucocutaneous lesions despite persistently elevated inflammatory markers. MRI revealed prolonged T1/T2 signals in the posterior horns of the lateral ventricles. During years of follow-up, the patient gradually developed characteristic BD manifestations while MRI showed progressive intracranial lesions, eventually presenting typical NBD imaging features concurrently with cerebral venous thrombosis. This atypical case highlights the necessity of early multimodal MRI and close clinical monitoring of focal lesions in the posterior horns of the lateral ventricles. When infectious causes are excluded, NBD should be considered. The rarity of this case improves clinicians’ ability to diagnose early NBD through MRI interpretation. Clinical trial This case report did not involve a clinical trial.